To Be or To Belong: Exploring the Consciousness of Being in Shafak’s The Island of Missing Trees through Sartrean Existentialism - Iftikhar, Shandana; Qureshi, Abdul Waheed; Ayaz, Maria (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
This study utilizes a qualitative research methodology, relying on interpretive analysis to explore existential themes in Elif Shafak’s The Island of Missing Trees. Framed through the lens of Jean-Paul Sartre’s existentialist philosophy, particularly his concept of consciousness of being. The research investigates how characters like Ada, Kostas, and Meryem confront their existence, make choices, and navigate the tension between being and belonging. Drawing on Barnet and Cain’s model of textual analysis, the study incorporates close reading, character development, thematic interpretation, symbolism, and narrative structure to reveal how the novel articulates Sartrean ideas of freedom, responsibility, and self-definition. The analysis highlights how Shafak gives voice to the characters’ internal struggle with identity and displacement, portraying consciousness not as a fixed state, but as a continuous process of becoming. Ultimately, the study demonstrates how literature becomes a vessel for existential inquiry, transforming abstract philosophical ideas into lived emotional realities.